A method for preparing low elastic modulus silicon nitride ceramics by 3D printing
The preparation of low elastic modulus silicon nitride ceramics through 3D printing technology has solved the problem that the elastic modulus of silicon nitride ceramics in the prior art is difficult to reduce, and the elastic modulus of silicon nitride ceramics is close to that of human bones, reducing the stress masking effect, and promoting bone healing.
Patent Information
- Application Number
- CN202411783948.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The prior art is difficult to reduce the elastic modulus of silicon nitride ceramics to close to the elastic modulus of human bones, resulting in a stress masking effect after human implantation, delaying bone healing.
The low elastic modulus silicon nitride ceramic is prepared by 3D printing technology. The method includes preparing surface-coated silicon nitride powder, spray granulation, preparing silicon nitride slurry and 3D printing, and finally obtaining silicon nitride ceramics by degreasing and sintering.
The elastic modulus of silicon nitride ceramics is reduced to 35.8-43.5GPa, which is close to the elastic modulus of human bones, reduces the stress masking effect and promotes bone healing.
Smart Images

Figure CN119241258B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of silicon nitride ceramics, and in particular to a method for preparing low elastic modulus silicon nitride ceramics by 3D printing. Background Art
[0002] Silicon nitride is a high-performance ceramic material with excellent mechanical, thermal and chemical properties. It also has extremely high tensile strength and hardness, which enables it to remain stable under high stress conditions. Compared with other ceramic materials, silicon nitride has higher fracture toughness and can resist mechanical and thermal shock. Silicon nitride has a low density, which makes it advantageous in weight-sensitive applications. With its excellent thermal and mechanical properties, silicon nitride is widely used in mechanical engineering, electronics industry, medical equipment and chemical industry.
[0003] Silicon nitride ceramics have a high intrinsic elastic modulus, which can reach 310GPa. When used in human body implants in the field of medical devices, since the intrinsic elastic modulus of silicon nitride ceramics is much higher than that of bones, they bear most of the mechanical load after being implanted in the human body, resulting in a reduction in the load on the bones, forming a stress shielding effect, which further delays bone healing. Over time, the bones become porous.
[0004] In order to reduce the elastic modulus of silicon nitride ceramics, there are currently two commonly used methods: the first method is to adjust the powder formula, change the type and content of sintering aids, and reduce the elastic modulus of silicon nitride by controlling the components; the second method is to add pore-forming agents to make the pores inside the sintered silicon nitride unevenly distributed, thereby reducing the elastic modulus of silicon nitride; the third method is to use special processes, such as freeze-drying, to prepare porous silicon nitride with directional pore distribution, thereby reducing the elastic modulus of silicon nitride; the fourth method is to use 3D printing technology to prepare silicon nitride with a grid structure to reduce the elastic modulus.
[0005] However, the above technology has limited effect on reducing the elastic modulus of silicon nitride ceramics, and it is difficult to reduce the elastic modulus of silicon nitride ceramics to a level close to that of human bones. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a method for preparing low elastic modulus silicon nitride ceramics by 3D printing, which can reduce the elastic modulus of silicon nitride ceramics to a level close to that of human bone.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0008] A method for preparing low elastic modulus silicon nitride ceramics by 3D printing, comprising the following steps: preparing surface-coated silicon nitride powder, spray granulation, preparing silicon nitride slurry, and 3D printing:
[0009] The method for preparing the surface-coated silicon nitride powder comprises adding a metal nitrate to an alcohol solvent, stirring at 40-50° C. for 30-35 minutes, adding silicon nitride powder, continuing to stir for 30-35 minutes, dropping a coprecipitant at a temperature of 40-50° C., continuing to stir for 30-35 minutes after the dropping is completed, filtering by suction, drying the filter residue at 100-105° C., and then heat-treating the residue to obtain the surface-coated silicon nitride powder;
[0010] The heat treatment is carried out under air atmosphere, with the temperature being raised to 500-700°C at a rate of 1-1.5°C / min, and the heat treatment is carried out at 500-700°C for 2-2.5h;
[0011] The metal nitrate is one of yttrium nitrate, aluminum nitrate, lanthanum nitrate, erbium nitrate and magnesium nitrate;
[0012] The alcohol solvent is methanol or ethanol;
[0013] The molar ratio of the metal cation in the metal nitrate to the silicon nitride powder is 6-10:90-94;
[0014] The D50 particle size of the silicon nitride powder is ≤1 μm;
[0015] The mass volume ratio of the silicon nitride powder to the alcohol solution is 100-120 g:500 mL;
[0016] The coprecipitant is one of ammonia water, ethanol solution of urea, and ethylenediamine;
[0017] The mass concentration of the ammonia water is 25-28%;
[0018] The mass concentration of the urea ethanol solution is 30-40%;
[0019] The dropping speed of the coprecipitant is 1-1.5 mL / min;
[0020] The spray granulation is to spray granulate the surface-coated silicon nitride powder, control the inlet temperature in the spray granulation to be 125-175°C, the outlet temperature to be 100-150°C, the air pressure to be 1.2-3MP, the sprayer frequency to be 200-220Hz, and obtain spheroidized silicon nitride particles after the spray granulation is completed;
[0021] The D50 particle size of the spheroidized silicon nitride particles is ≤5 μm;
[0022] The silicon nitride slurry is prepared by adding a resin to the spheroidized silicon nitride particles, then adding ethyl 2,4,6-trimethylbenzoylphenylphosphonate (TPO-L), a dispersant, and a spherical pore-forming agent, and then using a slurry processing system to prepare the slurry to obtain a ceramic slurry;
[0023] The resin is a composition of 1,6-hexanediol diacrylate (HDDA), ethoxylated pentaerythritol tetraacrylate (PPTTA), and 4-acryloylmorpholine (ACMO), wherein the mass ratio of 1,6-hexanediol diacrylate (HDDA), ethoxylated pentaerythritol tetraacrylate (PPTTA), and 4-acryloylmorpholine (ACMO) is 3.8-4.2:3.8-4.2:2;
[0024] The mass fraction of 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester (TPO-L) to the total mass of the resin is 0.9-1.1%;
[0025] The mass ratio of the mass of the spheroidized silicon nitride particles to the total mass of the resin is 65-67:34;
[0026] The dispersant is BYK-103 dispersant;
[0027] The mass fraction of the dispersant to the mass of the silicon nitride powder in the spheroidized silicon nitride particles is 1.9-2.1%;
[0028] The spherical pore-forming agent is PMMA microbeads, and the D50 particle size is 10-20 μm;
[0029] The mass fraction of the spherical pore former to the mass of the silicon nitride powder in the spheroidized silicon nitride particles is 20-30%;
[0030] The volume solid content of the ceramic slurry is 40-45%;
[0031] The 3D printing is to pour the ceramic slurry into the printing bin of the 3D printer, ensure that there are no bubbles in the bin, and then start the printing process after calibration. After the printing is completed, the blank is removed, cleaned with a cleaning solution, degreased and sintered to obtain silicon nitride ceramics;
[0032] The degreasing and sintering temperature is 1700-1800° C., and the heat preservation time is 2-2.5 hours.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] (1) The method of preparing low elastic modulus silicon nitride ceramics by 3D printing of the present invention, by compounding a sintering aid with silicon nitride powder, using PMMA microbeads as a pore-forming agent and using 3D printing to form, the three methods can play a synergistic role in reducing the elastic modulus of silicon nitride ceramics. Among them, in compounding the sintering aid with silicon nitride powder, firstly, the metal nitrate is combined with the silicon nitride powder, and the metal cation is adsorbed on the surface of the silicon nitride powder, and then a coprecipitant is added, and the coprecipitant promotes the precipitation of the metal nitrate, and a spheroidization is performed to obtain a silicon nitride powder with a metal oxide coated on the surface, and then the silicon nitride powder coated with the metal oxide is mixed with PMMA microspheres, and the silicon nitride powder coated with the metal oxide is adsorbed on the surface of the PMMA microspheres, and a secondary spheroidization is performed to obtain spheroidized silicon nitride particles, thereby improving the dispersion uniformity of the silicon nitride powder and the PMMA microspheres and the flow rate of the silicon nitride particles in 3D printing, which is more conducive to the 3D printing, thereby playing a synergistic role;
[0035] (2) The method of preparing low elastic modulus silicon nitride ceramics by 3D printing of the present invention can reduce the elastic modulus of silicon nitride ceramics. The elastic modulus of the prepared silicon nitride ceramics is 35.8-43.5 GPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a SEM image of the silicon nitride ceramic prepared in Example 1;
[0037] Figure 2 This is a physical picture of the silicon nitride ceramic prepared in Example 1. DETAILED DESCRIPTION
[0038] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0039] Example 1
[0040] A method for preparing low elastic modulus silicon nitride ceramics by 3D printing, specifically:
[0041] 1. Preparation of surface-coated silicon nitride powder: Add metal nitrate to alcohol solvent, stir at 40°C for 30 minutes, add silicon nitride powder, continue stirring for 30 minutes, drop coprecipitant at 40°C, control the drop rate to 1 mL / min, continue stirring for 30 minutes after the drop addition, filter, dry the filter residue at 100°C, and then heat treat to obtain surface-coated silicon nitride powder;
[0042] The heat treatment is carried out under air atmosphere, with the temperature being raised to 500°C at a rate of 1°C / min, and the heat treatment is carried out at 500°C for 2h;
[0043] The metal nitrate is yttrium nitrate;
[0044] The alcohol solvent is methanol;
[0045] The molar ratio of the metal cation in the metal nitrate to the silicon nitride powder is 6:90;
[0046] The D50 particle size of the silicon nitride powder is 0.5 μm;
[0047] The mass volume ratio of the silicon nitride powder to the alcohol solution is 100g:500mL;
[0048] The coprecipitant is aqueous ammonia;
[0049] The mass concentration of the ammonia water is 25%;
[0050] 2. Spray granulation: The surface-coated silicon nitride powder is spray granulated, and the inlet temperature during the spray granulation is controlled to be 125°C, the outlet temperature is 100°C, the air pressure is 1.2MP, and the sprayer frequency is 200Hz. After the spray granulation is completed, spheroidized silicon nitride particles are obtained;
[0051] The D50 particle size of the spheroidized silicon nitride particles is 2 μm;
[0052] 3. Prepare silicon nitride slurry: add resin to spheroidized silicon nitride particles, then add ethyl 2,4,6-trimethylbenzoylphenylphosphonate (TPO-L), a dispersant, and a spherical pore-forming agent, and then use a slurry processing system to prepare the slurry to obtain a ceramic slurry;
[0053] The resin is a composition of 1,6-hexanediol diacrylate (HDDA), ethoxylated pentaerythritol tetraacrylate (PPTTA), and 4-acryloylmorpholine (ACMO), wherein the mass ratio of 1,6-hexanediol diacrylate (HDDA), ethoxylated pentaerythritol tetraacrylate (PPTTA), and 4-acryloylmorpholine (ACMO) is 3.8:3.8:2;
[0054] The mass fraction of 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester (TPO-L) in the total mass of the resin is 0.9%;
[0055] The mass ratio of the spheroidized silicon nitride particles to the total mass of the resin is 65:34;
[0056] The dispersant is BYK-103 dispersant;
[0057] The mass fraction of the dispersant to the mass of the silicon nitride powder in the spheroidized silicon nitride particles is 1.9%;
[0058] The spherical pore-forming agent is PMMA microbeads, and the D50 particle size is 10 μm;
[0059] The mass fraction of the spherical pore former to the mass of the silicon nitride powder in the spheroidized silicon nitride particles is 20%;
[0060] The volume solid content of the ceramic slurry is 40%;
[0061] 4.3D printing: Pour the ceramic slurry into the printing silo of the 3D printer, make sure there are no bubbles in the silo, then calibrate and start the printing process. After printing is completed, remove the blank, clean it with cleaning fluid, degrease and sinter it to obtain silicon nitride ceramics;
[0062] The debinding sintering temperature is 1700° C. and the holding time is 2 hours.
[0063] The SEM image of the silicon nitride ceramic prepared in this example is shown in Figure 1 As shown; see the actual picture Figure 2 shown.
[0064] Example 2
[0065] A method for preparing low elastic modulus silicon nitride ceramics by 3D printing, specifically:
[0066] 1. Preparation of surface-coated silicon nitride powder: Add metal nitrate to alcohol solvent, stir at 40°C for 32 minutes, add silicon nitride powder, continue stirring for 32 minutes, drop coprecipitant at 40°C, control the drop rate to 1.2 mL / min, continue stirring for 32 minutes after the drop addition, filter, dry the filter residue at 102°C, and then heat treat to obtain surface-coated silicon nitride powder;
[0067] The heat treatment is carried out under air atmosphere by heating the temperature at a rate of 1.2°C / min to 550°C and performing the heat treatment at 550°C for 2h;
[0068] The metal nitrate is aluminum nitrate;
[0069] The alcohol solvent is methanol;
[0070] The molar ratio of the metal cation in the metal nitrate to the silicon nitride powder is 7:92;
[0071] The D50 particle size of the silicon nitride powder is 0.6 μm;
[0072] The mass volume ratio of the silicon nitride powder to the alcohol solution is 110 g:500 mL;
[0073] The coprecipitant is an ethanol solution of urea;
[0074] The mass concentration of the urea ethanol solution is 30%;
[0075] 2. Spray granulation: The surface-coated silicon nitride powder is spray granulated, and the inlet temperature during the spray granulation is controlled to be 135°C, the outlet temperature is 110°C, the air pressure is 1.5MP, and the sprayer frequency is 200Hz. After the spray granulation is completed, spheroidized silicon nitride particles are obtained;
[0076] The D50 particle size of the spheroidized silicon nitride particles is 3 μm;
[0077] 3. Prepare silicon nitride slurry: add resin to spheroidized silicon nitride particles, then add ethyl 2,4,6-trimethylbenzoylphenylphosphonate (TPO-L), a dispersant, and a spherical pore-forming agent, and then use a slurry processing system to prepare the slurry to obtain a ceramic slurry;
[0078] The resin is a composition of 1,6-hexanediol diacrylate (HDDA), ethoxylated pentaerythritol tetraacrylate (PPTTA), and 4-acryloylmorpholine (ACMO), wherein the mass ratio of 1,6-hexanediol diacrylate (HDDA), ethoxylated pentaerythritol tetraacrylate (PPTTA), and 4-acryloylmorpholine (ACMO) is 3.9:3.9:2;
[0079] The mass fraction of 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester (TPO-L) in the total mass of the resin is 1%;
[0080] The mass ratio of the spheroidized silicon nitride particles to the total mass of the resin is 66:34;
[0081] The dispersant is BYK-103 dispersant;
[0082] The mass fraction of the mass of the dispersant to the mass of the silicon nitride powder in the spheroidized silicon nitride particles is 2%;
[0083] The spherical pore-forming agent is PMMA microbeads, and the D50 particle size is 12 μm;
[0084] The mass fraction of the spherical pore former to the mass of the silicon nitride powder in the spheroidized silicon nitride particles is 22%;
[0085] The volume solid content of the ceramic slurry is 42%;
[0086] 4.3D printing: Pour the ceramic slurry into the printing silo of the 3D printer, make sure there are no bubbles in the silo, then calibrate and start the printing process. After printing is completed, remove the blank, clean it with cleaning fluid, degrease and sinter it to obtain silicon nitride ceramics;
[0087] The debinding sintering temperature is 1700° C. and the holding time is 2 hours.
[0088] Example 3
[0089] A method for preparing low elastic modulus silicon nitride ceramics by 3D printing, specifically:
[0090] 1. Preparation of surface-coated silicon nitride powder: Add metal nitrate to alcohol solvent, stir at 45°C for 35 minutes, add silicon nitride powder, continue stirring for 35 minutes, drop coprecipitant at 45°C, control the drop rate to 1.4 mL / min, continue stirring for 35 minutes after the drop addition, filter, dry the filter residue at 105°C, and then heat treat to obtain surface-coated silicon nitride powder;
[0091] The heat treatment is carried out under air atmosphere, with the temperature being raised to 600°C at a rate of 1°C / min, and the heat treatment is carried out at 600°C for 2.5 hours;
[0092] The metal nitrate is lanthanum nitrate;
[0093] The alcohol solvent is ethanol;
[0094] The molar ratio of the metal cation in the metal nitrate to the silicon nitride powder is 8:93;
[0095] The D50 particle size of the silicon nitride powder is 1 μm;
[0096] The mass volume ratio of the silicon nitride powder to the alcohol solution is 115g:500mL;
[0097] The coprecipitant is aqueous ammonia;
[0098] The mass concentration of the ammonia water is 28%;
[0099] 2. Spray granulation: The surface-coated silicon nitride powder is spray granulated, and the inlet temperature during the spray granulation is controlled to be 165°C, the outlet temperature is 140°C, the air pressure is 2.5MP, and the sprayer frequency is 200Hz. After the spray granulation is completed, spheroidized silicon nitride particles are obtained;
[0100] The D50 particle size of the spheroidized silicon nitride particles is 5 μm;
[0101] 3. Prepare silicon nitride slurry: add resin to spheroidized silicon nitride particles, then add ethyl 2,4,6-trimethylbenzoylphenylphosphonate (TPO-L), a dispersant, and a spherical pore-forming agent, and then use a slurry processing system to prepare the slurry to obtain a ceramic slurry;
[0102] The resin is a composition of 1,6-hexanediol diacrylate (HDDA), ethoxylated pentaerythritol tetraacrylate (PPTTA), and 4-acryloylmorpholine (ACMO), wherein the mass ratio of 1,6-hexanediol diacrylate (HDDA), ethoxylated pentaerythritol tetraacrylate (PPTTA), and 4-acryloylmorpholine (ACMO) is 4:4:2;
[0103] The mass fraction of 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester (TPO-L) in the total mass of the resin is 1%;
[0104] The mass ratio of the spheroidized silicon nitride particles to the total mass of the resin is 66:34;
[0105] The dispersant is BYK-103 dispersant;
[0106] The mass fraction of the mass of the dispersant to the mass of the silicon nitride powder in the spheroidized silicon nitride particles is 2%;
[0107] The spherical pore-forming agent is PMMA microbeads, and the D50 particle size is 20 μm;
[0108] The mass fraction of the spherical pore former to the mass of the silicon nitride powder in the spheroidized silicon nitride particles is 25%;
[0109] The volume solid content of the ceramic slurry is 44%;
[0110] 4.3D printing: Pour the ceramic slurry into the printing silo of the 3D printer, make sure there are no bubbles in the silo, then calibrate and start the printing process. After printing is completed, remove the blank, clean it with cleaning fluid, degrease and sinter it to obtain silicon nitride ceramics;
[0111] The debinding sintering temperature is 1750° C. and the holding time is 2.5 h.
[0112] Example 4
[0113] A method for preparing low elastic modulus silicon nitride ceramics by 3D printing, specifically:
[0114] 1. Preparation of surface-coated silicon nitride powder: Add metal nitrate to alcohol solvent, stir at 48°C for 30 minutes, add silicon nitride powder, continue stirring for 30 minutes, drop coprecipitant at 48°C, control the drop rate to 1.2 mL / min, continue stirring for 34 minutes after the drop addition, filter, dry the filter residue at 100°C, and then heat treat to obtain surface-coated silicon nitride powder;
[0115] The heat treatment is carried out under air atmosphere, with the temperature being raised to 700°C at a rate of 1°C / min, and the heat treatment is carried out at 700°C for 2.5 hours;
[0116] The metal nitrate is erbium nitrate;
[0117] The alcohol solvent is ethanol;
[0118] The molar ratio of the metal cation in the metal nitrate to the silicon nitride powder is 9:93;
[0119] The D50 particle size of the silicon nitride powder is 1 μm;
[0120] The mass volume ratio of the silicon nitride powder to the alcohol solution is 110 g:500 mL;
[0121] The coprecipitant is ethylenediamine;
[0122] 2. Spray granulation: The surface-coated silicon nitride powder is spray granulated, and the inlet temperature during the spray granulation is controlled to be 170°C, the outlet temperature is 140°C, the air pressure is 2.5MP, and the sprayer frequency is 200Hz. After the spray granulation is completed, spheroidized silicon nitride particles are obtained;
[0123] The D50 particle size of the spheroidized silicon nitride particles is 5 μm;
[0124] 3. Prepare silicon nitride slurry: add resin to spheroidized silicon nitride particles, then add ethyl 2,4,6-trimethylbenzoylphenylphosphonate (TPO-L), a dispersant, and a spherical pore-forming agent, and then use a slurry processing system to prepare the slurry to obtain a ceramic slurry;
[0125] The resin is a composition of 1,6-hexanediol diacrylate (HDDA), ethoxylated pentaerythritol tetraacrylate (PPTTA), and 4-acryloylmorpholine (ACMO), wherein the mass ratio of 1,6-hexanediol diacrylate (HDDA), ethoxylated pentaerythritol tetraacrylate (PPTTA), and 4-acryloylmorpholine (ACMO) is 4.2:4.2:2;
[0126] The mass fraction of 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester (TPO-L) in the total mass of the resin is 1%;
[0127] The mass ratio of the spheroidized silicon nitride particles to the total mass of the resin is 67:34;
[0128] The dispersant is BYK-103 dispersant;
[0129] The mass fraction of the dispersant to the mass of the silicon nitride powder in the spheroidized silicon nitride particles is 2.1%;
[0130] The spherical pore-forming agent is PMMA microbeads, and the D50 particle size is 20 μm;
[0131] The mass fraction of the spherical pore former to the mass of the silicon nitride powder in the spheroidized silicon nitride particles is 30%;
[0132] The volume solid content of the ceramic slurry is 45%;
[0133] 4.3D printing: Pour the ceramic slurry into the printing silo of the 3D printer, make sure there are no bubbles in the silo, then calibrate and start the printing process. After printing is completed, remove the blank, clean it with cleaning fluid, degrease and sinter it to obtain silicon nitride ceramics;
[0134] The debinding sintering temperature is 1800° C. and the holding time is 2 hours.
[0135] Example 5
[0136] A method for preparing low elastic modulus silicon nitride ceramics by 3D printing, specifically:
[0137] 1. Preparation of surface-coated silicon nitride powder: Add metal nitrate to alcohol solvent, stir at 50°C for 35 minutes, add silicon nitride powder, continue stirring for 35 minutes, drop coprecipitant at 50°C, control the drop rate to 1.5mL / min, continue stirring for 35 minutes after the drop addition, filter, dry the filter residue at 105°C, and then heat treat to obtain surface-coated silicon nitride powder;
[0138] The heat treatment is carried out under air atmosphere, with the temperature being raised to 700°C at a rate of 1.5°C / min, and the heat treatment is carried out at 700°C for 2.5 hours;
[0139] The metal nitrate is magnesium nitrate;
[0140] The alcohol solvent is ethanol;
[0141] The molar ratio of the metal cation in the metal nitrate to the silicon nitride powder is 10:94;
[0142] The D50 particle size of the silicon nitride powder is 1 μm;
[0143] The mass volume ratio of the silicon nitride powder to the alcohol solution is 120g:500mL;
[0144] The coprecipitant is an ethanol solution of urea;
[0145] The mass concentration of the urea ethanol solution is 40%;
[0146] 2. Spray granulation: The surface-coated silicon nitride powder is spray granulated, and the inlet temperature during the spray granulation is controlled to be 175°C, the outlet temperature is 150°C, the air pressure is 3MP, and the sprayer frequency is 220Hz. After the spray granulation is completed, spheroidized silicon nitride particles are obtained;
[0147] The D50 particle size of the spheroidized silicon nitride particles is 5 μm;
[0148] 3. Prepare silicon nitride slurry: add resin to spheroidized silicon nitride particles, then add ethyl 2,4,6-trimethylbenzoylphenylphosphonate (TPO-L), a dispersant, and a spherical pore-forming agent, and then use a slurry processing system to prepare the slurry to obtain a ceramic slurry;
[0149] The resin is a composition of 1,6-hexanediol diacrylate (HDDA), ethoxylated pentaerythritol tetraacrylate (PPTTA), and 4-acryloylmorpholine (ACMO), wherein the mass ratio of 1,6-hexanediol diacrylate (HDDA), ethoxylated pentaerythritol tetraacrylate (PPTTA), and 4-acryloylmorpholine (ACMO) is 4.2:4.2:2;
[0150] The mass fraction of 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester (TPO-L) in the total mass of the resin is 1.1%;
[0151] The mass ratio of the spheroidized silicon nitride particles to the total mass of the resin is 67:34;
[0152] The dispersant is BYK-103 dispersant;
[0153] The mass fraction of the dispersant to the mass of the silicon nitride powder in the spheroidized silicon nitride particles is 2.1%;
[0154] The spherical pore-forming agent is PMMA microbeads, and the D50 particle size is 20 μm;
[0155] The mass fraction of the spherical pore former to the mass of the silicon nitride powder in the spheroidized silicon nitride particles is 20-30%;
[0156] The volume solid content of the ceramic slurry is 45%;
[0157] 4.3D printing: Pour the ceramic slurry into the printing silo of the 3D printer, make sure there are no bubbles in the silo, then calibrate and start the printing process. After printing is completed, remove the blank, clean it with cleaning fluid, degrease and sinter it to obtain silicon nitride ceramics;
[0158] The degreasing sintering temperature is 1800° C. and the holding time is 2.5 hours.
[0159] Comparative Example 1
[0160] On the basis of Example 1, in the step 1 of preparing the surface-coated silicon nitride powder, the addition of metal nitrate and coprecipitant is omitted, and yttrium oxide is additionally added; the step 3 of preparing silicon nitride slurry and the step 4 of 3D printing are omitted, and the step 3 of molding is added;
[0161] Specifically, the step of surface-coating silicon nitride powder in step 1 is changed to:
[0162] The metal oxide is added to an alcohol solvent, stirred at 50°C for 30 minutes, silicon nitride powder is added, stirred for 30 minutes, filtered, and the filter residue is dried at 100°C and then heat-treated to obtain surface-coated silicon nitride powder;
[0163] The heat treatment is carried out under air atmosphere, with the temperature being raised to 500°C at a rate of 1°C / min, and the heat treatment is carried out at 500°C for 2h;
[0164] The metal oxide is yttrium oxide;
[0165] The D50 particle size of the yttrium oxide is 0.5 μm;
[0166] The alcohol solvent is methanol;
[0167] The molar ratio of the metal cation in the metal oxide to the silicon nitride powder is 6:90;
[0168] The D50 particle size of the silicon nitride powder is 0.5 μm;
[0169] The mass volume ratio of the silicon nitride powder to the alcohol solution is 100g:500mL;
[0170] Specifically, change the molding step 3 to:
[0171] A pore-forming agent is added to the spheroidized silicon nitride particles, and the particles are added into a mold after being stirred evenly for cold isostatic pressing. The pressure of the cold isostatic pressing is controlled to be 100 MPa, and then the particles are kept at 1700° C. for 2 hours to obtain silicon nitride ceramics.
[0172] The pore-forming agent is starch;
[0173] The mass fraction of the pore former in the spheroidized silicon nitride particles is 20%.
[0174] The rest of the technical solutions are consistent with those in Example 5.
[0175] Comparative Example 2
[0176] On the basis of Example 1, in the step of preparing the surface-coated silicon nitride powder in step 1, the addition of metal nitrate and coprecipitant is omitted, and yttrium oxide is additionally added;
[0177] Specifically, the step of surface-coating silicon nitride powder in step 1 is changed to:
[0178] The metal oxide is added to an alcohol solvent, stirred at 50°C for 30 minutes, silicon nitride powder is added, stirred for 30 minutes, filtered, and the filter residue is dried at 100°C and then heat-treated to obtain surface-coated silicon nitride powder;
[0179] The heat treatment is carried out under air atmosphere, with the temperature being raised to 500°C at a rate of 1°C / min, and the heat treatment is carried out at 500°C for 2h;
[0180] The metal oxide is yttrium oxide;
[0181] The D50 particle size of the metal oxide is 0.5 μm;
[0182] The alcohol solvent is methanol;
[0183] The molar ratio of the metal cation in the metal oxide to the silicon nitride powder is 6:90;
[0184] The D50 particle size of the silicon nitride powder is 0.5 μm;
[0185] The mass volume ratio of the silicon nitride powder to the alcohol solution is 100g:500mL.
[0186] The rest of the technical solutions are consistent with those in Example 5.
[0187] Comparative Example 3
[0188] On the basis of Example 1, in the step of preparing silicon nitride slurry in step 3, starch or the like is used to replace the addition of spherical pore-forming agent, and the step of preparing silicon nitride slurry in step 3 is specifically changed to:
[0189] Adding resin to spheroidized silicon nitride particles, and then adding ethyl 2,4,6-trimethylbenzoylphenylphosphonate (TPO-L), a dispersant, and a pore-forming agent, and then preparing a slurry using a slurry processing system to obtain a ceramic slurry;
[0190] The resin is a composition of 1,6-hexanediol diacrylate (HDDA), ethoxylated pentaerythritol tetraacrylate (PPTTA), and 4-acryloylmorpholine (ACMO), wherein the mass ratio of 1,6-hexanediol diacrylate (HDDA), ethoxylated pentaerythritol tetraacrylate (PPTTA), and 4-acryloylmorpholine (ACMO) is 3.8:3.8:2;
[0191] The mass fraction of 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester (TPO-L) in the total mass of the resin is 0.9%;
[0192] The mass ratio of the spheroidized silicon nitride particles to the total mass of the resin is 65:34;
[0193] The dispersant is BYK-103 dispersant;
[0194] The mass fraction of the mass of the dispersant to the mass of the silicon nitride powder in the spheroidized silicon nitride particles is 2%;
[0195] The pore-forming agent is starch;
[0196] The mass fraction of the pore-forming agent to the mass of the silicon nitride powder in the spheroidized silicon nitride particles is 20%;
[0197] The volume solid content of the ceramic slurry is 40%.
[0198] The rest of the technical solutions are consistent with those in Example 5.
[0199] Comparative Example 4
[0200] On the basis of Example 1, the third step of preparing silicon nitride slurry and the fourth step of 3D printing are omitted, and the third step of molding is added;
[0201] Specifically, change the molding step 3 to:
[0202] Add a spherical pore-forming agent to the spheroidized silicon nitride particles, stir them evenly, and then add them into a mold for cold isostatic pressing. The pressure of the cold isostatic pressing is controlled to be 100 MPa, and then the temperature is kept at 1700° C. for 2 hours to obtain silicon nitride ceramics.
[0203] The spherical pore-forming agent is PMMA microbeads, and the D50 particle size is 10 μm;
[0204] The mass fraction of the spherical pore former to the mass of the silicon nitride powder in the spheroidized silicon nitride particles is 20%.
[0205] The rest of the technical solutions are consistent with those in Example 5.
[0206] Performance Testing
[0207] The elastic modulus of the silicon nitride ceramics prepared in Examples 1-5 and Comparative Examples 1-4 was tested, and the elastic modulus of human bone and the elastic modulus of titanium were added for comparison. The test and comparison results are shown in Table 1.
[0208] Table 1
[0209]
[0210] It can be seen from the performance test results that compared with Example 1, Comparative Example 1 did not compound the sintering aid with the silicon nitride powder, did not use PMMA microbeads as a pore-forming agent, and did not use 3D printing. The elastic modulus of the prepared silicon nitride ceramic is the largest.
[0211] Compared with Example 1, Comparative Example 2 does not compound the sintering aid with the silicon nitride powder; Compared with Example 1, Comparative Example 3 does not use PMMA microbeads as a pore-forming agent; Compared with Example 1, Comparative Example 4 does not use 3D printing molding; The elastic modulus of the silicon nitride ceramics prepared in Comparative Examples 2-4 is greater than that of the silicon nitride ceramics prepared in Example 1.
[0212] Compared with comparative examples 1-4 and titanium metal, the elastic modulus of the silicon nitride ceramics prepared in Examples 1-5 is closer to the elastic modulus of human bones. When used as human implants, the stress shielding effect can be avoided to a limited extent. At the same time, the macroscopic and microscopic pore structures of silicon nitride ceramics are also more conducive to the growth of bone tissue, thereby better playing the role of the implant.
[0213] Unless otherwise specified, all percentages used in the present invention are by mass.
[0214] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing low elastic modulus silicon nitride ceramics by 3D printing, characterized in that: The process consists of the following steps: preparation of surface-coated silicon nitride powder, spray granulation, preparation of silicon nitride slurry, and 3D printing: The method for preparing the surface-coated silicon nitride powder comprises adding a metal nitrate to an alcohol solvent, stirring at 40-50° C., adding silicon nitride powder, continuing stirring, dropping a coprecipitant at a temperature of 40-50° C., continuing stirring after the dropping, filtering, drying the filter residue, and then subjecting the filter residue to heat treatment to obtain the surface-coated silicon nitride powder; The D50 particle size of the silicon nitride powder is ≤1 μm; The metal nitrate is one of yttrium nitrate, aluminum nitrate, lanthanum nitrate, erbium nitrate and magnesium nitrate; The alcohol solvent is methanol or ethanol; The molar ratio of the metal cation in the metal nitrate to the silicon nitride powder is 6-10:90-94; The heat treatment is carried out under air atmosphere, with the temperature being raised to 500-700°C at a rate of 1-1.5°C / min, and the heat treatment is carried out at 500-700°C for 2-2.5h; The mass volume ratio of the silicon nitride powder to the alcohol solution is 100-120 g:500 mL; The coprecipitant is one of ammonia water, ethanol solution of urea, and ethylenediamine; The spray granulation is to spray granulate the silicon nitride powder coated on the surface, and spheroidized silicon nitride particles are obtained after the spray granulation is completed; The D50 particle size of the spheroidized silicon nitride particles is ≤5 μm; The silicon nitride slurry is prepared by adding a resin to the spheroidized silicon nitride particles, then adding ethyl 2,4,6-trimethylbenzoylphenylphosphonate, a dispersant, and a spherical pore-forming agent, and then using a slurry processing system to prepare the slurry to obtain a ceramic slurry; The spherical pore-forming agent is PMMA microbeads, and the D50 particle size is 10-20 μm; The mass fraction of the spherical pore former to the mass of the silicon nitride powder in the spheroidized silicon nitride particles is 20-30%.
2. The method for preparing low elastic modulus silicon nitride ceramics by 3D printing according to claim 1, characterized in that: The mass concentration of the ammonia water is 25-28%; The mass concentration of the urea ethanol solution is 30-40%; The dropping speed of the coprecipitant is 1-1.5 mL / min.
3. The method for preparing low elastic modulus silicon nitride ceramics by 3D printing according to claim 1, characterized in that: The inlet temperature in the spray granulation is 125-175° C., the outlet temperature is 100-150° C., the air pressure is 1.2-3 MPa, and the sprayer frequency is 200-220 Hz.
4. The method for preparing low elastic modulus silicon nitride ceramics by 3D printing according to claim 1, characterized in that: The resin is a composition of 1,6-hexanediol diacrylate, ethoxylated pentaerythritol tetraacrylate and 4-acryloylmorpholine, wherein the mass ratio of 1,6-hexanediol diacrylate, ethoxylated pentaerythritol tetraacrylate and 4-acryloylmorpholine is 3.8-4.2:3.8-4.2:
2.
5. The method for preparing low elastic modulus silicon nitride ceramics by 3D printing according to claim 1, characterized in that: The mass fraction of ethyl 2,4,6-trimethylbenzoylphenylphosphonate to the total mass of the resin is 0.9-1.1%; The mass ratio of the mass of the spheroidized silicon nitride particles to the total mass of the resin is 65-67:34; The dispersant is BYK-103 dispersant; The mass fraction of the dispersant to the mass of the silicon nitride powder in the spheroidized silicon nitride particles is 1.9-2.1%; The volume solid content of the ceramic slurry is 40-45%.
6. The method for preparing low elastic modulus silicon nitride ceramics by 3D printing according to claim 1, characterized in that: The 3D printing is to pour the ceramic slurry into the printing silo of the 3D printer, ensure that there are no bubbles in the silo, and then start the printing process after calibration. After the printing is completed, the green body is removed, cleaned, degreased and sintered to obtain silicon nitride ceramics.
7. The method for preparing low elastic modulus silicon nitride ceramics by 3D printing according to claim 6, characterized in that: The degreasing and sintering temperature is 1700-1800° C., and the heat preservation time is 2-2.5 hours.
Citation Information
Patent Citations
Photo-cured silicon nitride ceramic slurry, silicon nitride ceramic and preparation method thereof
CN108892515A
Combined porous interbody fusion cage and manufacturing method thereof
CN117771027A